Watchful waiting in carefully selected metachronous cystadenolymphomas of the parotid gland: a reliable option?. Issue 5 (June 2019) - Mantsopoulos, K.; Goncalves, M.; Koch, M.; Iro, H.
Abstract: The aim of this study was to evaluate the potential of watchful waiting in the treatment of metachronous cystadenolymphomas, taking the experience of our department into consideration. All patients suspected of having a metachronous cystadenolymphoma, and who had a minimum follow-up time of 12 months, were studied (n = 26). Data about the growth rate, number of lesions, and symptoms of inflammation were recorded. Mean (range) follow-up was 36 (13–94) months. Metachronous tumours developed in three cases on the ipsilateral side, in 22 cases on the contralateral side, and on both sides in one case. The mean rate of growth /lesion was 15% /year (range: 22%–158%). There were no signs of local inflammation. The extreme variability in the behaviour of metachronous cystadenolymphomas points to the need for an individualised approach, accurate investigation of the sonographic characteristics, and continuous watchful waiting in affected patients.